PENGARUH INDEPENDENSI DAN INTEGRITAS TERHADAP KINERJA PENGAWASAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Okta Adi Saputra; Sri Rahayu; Susfa Yetti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
A high level of voluntary disclosure can indeed increase the transparency of the his study aims to determine the influence of independence and integrity on the performance of supervision through motivation as an intervening variable at the Provincial Inspectorate of Jambi. The approach used in this research is a quantitative approach. The data used in this study are the results of questionnaires filled out by auditors and P2UPD (Regional Government Internal Supervisory Apparatus). The data collection technique employed is the distribution of written statement questionnaires. Subsequently, the data analysis technique used is SmartPLS version 4. The results of this study indicate that the variables of independence and integrity affect the performance of supervision. However, the motivation variable does not affect the performance of supervision. Furthermore, the variable of independence through motivation on the performance of supervision and the variable of integrity through motivation do not affect the performance of supervision. Keywords: Independence, Integrity, Supervision performance, Motivation